TEKNOLOGI PEMBUATAN TEPUNG PORANG TERMODIFIKASI DENGAN VARIASI METODE PENGGILINGAN DAN LAMA FERMENTASI - Muh Agus Ferdian; Randhiki Gusti Perdana (BPFP Faperta UNIB, 2021)
Indonesia has many natural resources that have not been properly addressed or utilized, one of them is the Porang tuber. Porang tuber has the characteristic of araceae which has a high calcium crystal oxalate, that is 0.19%. These substances can cause itching and burning sensation in the mouth, even harm our kidneys. Thus, technology is needed to reduce the calcium oxalate content of Porang flour by modifying the processing method. The aims of this study are to obtain the most optimal technology for making modified porang flour with a decrease in optimal calcium oxalate levels and to know the physicochemical characteristics of the modified porang flour.. The research was carried out in three stages, namely the production process of Porang flour modified with the variations of wet and dry milling methods, and the fermentation time that were 0, 6, 12, 18 and 24 hours. Characteristics of modified Porang flour include chemical and physical, and the final stage is data analysis. The result showed that the modified Porang flour processing technology with the highest decrease in calcium oxalate content was the wet milling method with the fermentation time of 18 hours and the value of 62.28%. The chemical characteristics of the modified proximate content of Porang flour showed that the levels of protein, fat, water, ash and carbohydrates were 9.34%, 0.49%, 12.50%, 3.59% and 74.09% respectively. The physical characteristics of porang flour are brownish white, a distinctive aroma of flour, powder form and a slightly salty taste.